Biomass Torrefaction Process, Product Properties, Reactor Types, and Moving Bed Reactor Design Concepts - Tumuluru, Jaya Shankar; Ghiasi, Bahman; Soelberg, Nick R.; Sokhansanj, Shahab (Frontiers in Energy Research, 2021)
Torrefaction, a thermal pretreatment process, is gaining attention as it improves the physical properties and chemical composition of biomass for recycling. During torrefaction, biomass is heated slowly in an inert or oxygen-deficit environment to a maximum temperature of 300°C. The torrefaction process creates a solid uniform product with lower moisture and higher energy content than the raw biomass. During torrefaction, moisture and some volatile organic compounds volatilize from the biomass. Depending on stoichiometry and other conditions, non-condensable gas species, including CO and CO2, are formed. The specific objectives of this research are to: 1) understand the impact of torrefaction on product quality in terms of the physical properties, chemical composition, and storage behavior of the biomass; 2) discuss the various reactors used for biomass torrefaction; and 3) develop a model for designing a moving bed torrefier, considering fundamental heat and mass transfer calculations. Torrefaction improves the physical properties, chemical composition, and energy and storage properties of biomass. Torrefaction of biomass at 300°C increases the energy content by about 30% as compared to the raw biomass. For example, when torrefied, the calorific value of the biomass increases from about 18–19 MJ/kg to about 20–24 MJ/kg. The torrefied material has a moisture content of about 1–3% wet basis (w.b.). The loss of the hydroxyl group during torrefaction makes the biomass hydrophobic. The brittle nature of the torrefied biomass makes it easier to grind. The devolatilization and carbonization reactions change the proximate and ultimate composition. The carbon content increases, whereas the hydrogen, oxygen, and nitrogen content of the biomass decreases. Despite its superior properties, the commercialization of torrefaction technology is slow due to challenges associated with reactor design and final product quality. The different types of reactors that are typically used for biomass torrefaction are the fixed bed, rotary drum, microwave, fluidized bed, and horizontal and vertical moving bed. The moving bed reactor has gained popularity among the different torrefaction reactor designs as it is easy to operate and scale. In addition, it helps produce a uniform torrefied product. In this paper, different moving bed torrefaction and gas recycle concepts are conceptualized to assess the features, advantages, and disadvantages of various design and operating concepts. These designs include example concepts for: 1) vertical and horizontal torrefaction reactors; 2) recycle of all or a portion of the torrefier off-gas; 3) counter and co-flowing gas and biomass in the torrefier; 4) controls for the system temperatures, pressures, flow rates, and gas compositions; and 5) the ability to sample the biomass feed, torrefied product, and gas streams for analysis as needed to investigate the thermal decomposition, physical behavior, and operational performance of the torrefaction system. The article also briefly describes the solid feed system, gas supply and recycle system, solid product management, torrefier gas monitoring, control system, and fugitive dust emissions control. The model presented in this paper includes a set of equations for basic calculations to configure the torrefaction reactor dimensions, such as diameter and height of the moving bed torrefier for different capacities based on target and calculated solids and gas velocities, residence times, and temperatures.